Multi-suspension facility and device used for carrying child and allowing child to lie down - JIN YANDONG (2017)
The invention relates to a multi-suspension facility and device used for carrying a child and allowing the child to lie down, in particular to a foldable baby stroller. Frames, wheels mounted on the frames, and a sitting and lying device allowing an infant to sit and lie down are included. The two sides of the sitting and lying device are hinged to the frames through at least two connecting rod assemblies correspondingly. The frames include the first frame and the second frame which are hinged together. The sitting and lying device is formed by sequentially hinging one end of a first seat support, a seat inner-left connecting rod, a seat outer-left connecting rod and one end of a second seat support through a first seat shaft, a second seat shaft, a third seat shaft and a fourth seat shaft and by sequentially hinging the other end of the first seat support, a seat inner-right connecting rod, a seat outer-right connecting rod and the other end of the second seat support through a fifth seat shaft, a sixth seat